2012
DOI: 10.1002/ajmg.a.35551
|View full text |Cite
|
Sign up to set email alerts
|

Map of autosomal recessive genetic disorders in Saudi Arabia: Concepts and future directions

Abstract: Saudi Arabia has a population of 27.1 million. Prevalence of many autosomal recessive disorders is higher than in other known populations. This is attributable to the high rate of consanguineous marriages (56%), the tribal structure, and large family size. Founder mutations have been recognized in many autosomal recessive disorders, many of which are overrepresented within certain tribes. On the other hand, allelic heterogeneity is also observed among common and rare autosomal recessive conditions. With the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 120 publications
2
46
0
Order By: Relevance
“…Though they have identified multiple rare coding region variants, none was found to be a causal mutation. Consanguineous celiac families in Saudi Arabia present a potential opportunity to identify rare genetic mutations owing to their large family size and tribal culture [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though they have identified multiple rare coding region variants, none was found to be a causal mutation. Consanguineous celiac families in Saudi Arabia present a potential opportunity to identify rare genetic mutations owing to their large family size and tribal culture [20]. …”
Section: Discussionmentioning
confidence: 99%
“…In this context, whole exome sequencing presented us with an opportunity to examine a consanguineous family to reveal the causal mutation for Celiac disease. Saudi Arabia, being the global epicenter of the consanguinity (>56% of all marriages are between 1 st cousins), has a higher incidence of newborns with autosomal recessive disorders [20]. Despite the increasing prevalence, genetic investigations carried out on Saudi CD patients are few [21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the Saudi population have shown that autosomal recessive and other major genetic disorders (58,61), inflammatory bowel disease (59), familial multiple sclerosis (60), bronchial asthma (62), congenital heart disease (63,67), hearing impairment (64), spina bifida (65), several problems of pregnancy (57,66) and schizophrenia (67), occur at a higher prevalence in consanguineous mating. These finding and others stress the need for decrease in the rate of consanguineous marriages in the Saudi population.…”
Section: Consanguinity Has Several Advantages and Several Factorsmentioning
confidence: 99%
“…The prevalence of many autosomal recessive disorders in Saudi Arabia is higher than in other known populations, which is attributable to the high rate of consanguineous marriages (56%), the tribal structure, and large family size [11]. Herein, we describe the molecular defects of a large cohort of patients with LS from Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%